E-Money Tab As An Attendance Tracker For Elementary School Students - Minsih Minsih; Fiki Nur Rahmawati; Rusnilawati Rusnilawati (Profesi Pendidikan Dasar, 2021)
This study aims to describe: 1) the process of using e-money tab, 2) the advantages and disadvantages of using the e-money tab, 3) the impacts of using the e-money tab. This study was conducted as a qualitative study facilitating a phenomenological research design. Data was collected through interviews, live observation and analysis of documents. Study subjects included the principal, the IT team and students of 1 Muhammadiyah Elementary School, Ketelan Surakarta (Elementary School of Muhammadiyah 1 Ketelan Surakarta) and was conducted on location. Results of this study showed that: a) the use of e-money tabs as an attendance tracker can only be accessed at school and requires a strong internet network, b) an advantage to the use of e-money tab as an attendance tracker is being able to track attendance of students with ease, allowing teachers to ensure discipline and parents to monitor the arrival and departure time of their children to and from school. On the other hand, a disadvantage to this system is the instability of the internet network especially when multiple students are using the e-money tab at the same time, causing error in the server, c) the e-money tab has impacted the process of attendance tracking, in which it has maintained and improved discipline of students.